Critics on Policy of Soy-Based Infant Formula in Indonesia: Compared to Australian and New Zealand Food Standards - Agnescia Clarissa Sera (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: World Health Organiza on (WHO) recommends breast milk as sole and the most complete infant food during the first 6 months. However, in certain circumstances, when breas eeding is not possible, not de- sired or not advised, infant formulas like those are made of soy can be given to newborns. However, the safety of long-term use soy-based formula has been argued due to the possible adverse effects of phytoestrogen, phytates and aluminum in human body as well as the consequences of agrochemicals residue. Therefore, those problems should be taken into account while developing, reviewing or amending policy of infant formulas. This ar cle re- views the adequacy of soy-based infant formula policy in Indonesia to an cipate issues in SIF consump on. Methods: Australian and New Zealand Food Standards Code was used to compared to the decree of Indonesian NADFC. The results were described narra vely and analyzed from the perspec ve of the author. Results: Accordingly, only small aspects of SIF are regulated in Indonesian policy. The use of SPI for SIF in In- donesia is not a compulsory though scien fically another source may trigger diarrhea in newborn baby. No clause related to aluminum content, zinc to copper ra o, isoflavone level, GM soy and pes cide residue found in In- donesian policy. Conclusion: Apparently, very limited provision regarding SIF has been covered by Indonesian policy. The regu- la on of SIF marketed and manufactured in Indonesia should be more specific and developed based on recent clinical and epidemiological studies. On the other hand, Indonesia needs a comprehensive system where society may par cipate in reviewing the laws.